Radiological assessment of wastes from copper mining in Iberian Pyrite Belt - Juan Antonio Ramírez-Pérez; Alejandro Barba-Lobo; Manuel Jesús Gázquez-González; Juan Pedro Bolívar (Heliyon, 2025)
The Iberian Pyrite Belt (IPB), located in SW Spain, is the geographical area where more mining activities related to polymetallic minerals have been developed from around 4000 years before present, being especially intense from the second half of 19th century, generating huge amounts of wastes stored along the basins of the Odiel and Tinto rivers. According to the radiological European Union regulation, and the international one, the polymetallic mining is considered as a NORM (Naturally Occurring Radioactive Material) activity, and therefore, it is necessary to carry out an evaluation of the radiological risks associated with these mining activities. To achieve this objective the waste repositories of several mining areas were sampled trying to obtain the most representative wastes of the study area (roasted pyrite, floating mud, slags, leached pyrite, between others). The activity concentrations of natural radionuclides and multielement composition of the collected samples were measured, and different radiological indexes were calculated (Raeq, Hex, Ic, Fc238U and Fc232Th). The main conclusion of this work has been that all these indexes are below the threshold stablished by regulation to assure an effective dose smaller than 1 mSv per year, and therefore the mining waste deposited in the IPB can be used in valorization processes for building materials without radiological restrictions.